Pain syndrome in multiple myeloma (results of a single-center study) - M. V. Soloveva; M. V. Solovev; E. Z. Irugova; A. A. Startsev; N. K. Arutyunyan; A. A. Krayzman; A. V. Abakumova; L. P. Mendeleeva (Онкогематология)
Background. One of the most common symptoms of multiple myeloma (MM) is pain. Bone pain is observed in 60– 80 % of patients at the disease onset. Neuropathic pain syndrome is also often found in MM.Aim. To characterize the pain syndrome in MM at the disease onset and various therapy stages.Materials and methods. From January 2019 to October 2021 a retrospective single-center study included 105 patients with newly diagnosed symptomatic MM (49 men, 56 women) aged from 26 to 83 years (median 58.5). Induction therapy in all patients was performed with bortezomib-containing regimens. High-dose chemotherapy with autologous hematopoietic stem cell transplantation (auto-HSCT) was performed in 44 patients. The Fisher–Freeman test was used to analyze contingency tables.Results. Pain syndrome of varying severity at the onset of MM was observed in 83 % of patients. The median time from the onset of pain to the diagnosis of MM was 120 days. In 62.5 % of patients with kidney damage and pain, analgesics (mainly nonsteroidal anti-inflammatory drugs) were used before the diagnosis of MM. In patients with pain syndrome, compared with patients without it, at the onset of MM, pathological fractures (p = 0.01), bone plasmacytomas (p = 0.0001), hypercalcemia (p = 0.03) were significantly more often detected, and stage III was diagnosed according to Durie– Salmon (p = 0.021). The incidence of peripheral toxic polyneuropathy was 35 %. Complete regression of polyneuropathy symptoms was observed in 19 % of patients, and a significant decrease – in another 62 % of cases. The main manifestation of pain syndrome during auto-HSCT was pain in the oral cavity due to mucositis of varying severity.Conclusion. Our study showed that MM patients mainly with stage III (86 % of cases) are referred for hospitalization to the National Medical Research Center for Hematology. Moreover, in 83 % of them the disease is accompanied by severe pain. More than a third of patients (35 %) developed bortezomib-induced peripheral polyneuropathy. Opioid analgesics are used for pain relief in the hospital, the indications for which were recorded in 45 % and 41 % of patients with MM during induction therapy and auto-HSCT, respectively.